In vitro Antioxidant, Anti-inflammatory and Antibacterial Activities of Microencapsulated Elaeocarpus tectorius (Lour.) Poir Leaf Extracts - Manoharan, Keerthana; Chitra, P (Asian Journal of Biological and Life Sciences)
The genus Elaeocarpus comprises nearly three-fifty flowering plant species native to the Tropical and Subtropical Asia and Pacific. Elaeocarpus tectorius (Lour.) Poir. is one of the least explored plants of this genus. The present study was aimed to explore the phytochemicals present in the leaves of the plant Elaeocarpus tectorius (Lour.) Poir. and to formulate chitosan-coated alginate microcapsules loaded with the leaf extracts. The antioxidant, anti-inflammatory and antibacterial activities of the leaf extracts and microcapsules were then assessed. The leaf extract was found to possess a spectrum of phytochemicals in good quantities, including phenolics, flavonoids and tannins. The formulated chitosan-alginate microcapsules were found to be oval, spherical in shape and they exhibited good scavenging activities against nitric oxide and hydrogen peroxide radicals. The leaf extracts and microcapsules also exhibited good anti-inflammatory potential through inhibition of albumin denaturation and antiproteinase action. A prominent zone of inhibition was observed in the agar well diffusion assay suggesting the antibacterial potential of the microcapsules. The current study showed that the ethanolic extract of E. tectorius leaves has significant antioxidant, anti-inflammatory and antibacterial activities. Many biologically active secondary metabolites were present in the leaf extract which could be responsible for its therapeutic potential. Microencapsulation has protected and enhanced the biological properties of the leaf extracts as indicated by the increased scavenging, anti-inflammatory and antibacterial potential of the microcapsules.
Keywords: Antibiotics; Antioxidants; Chitosan; Inflammation; Medicinal plants; Microencapsulation; Phytochemicals; Sodium alginate